Analisis Peranan Koperasi Simpan Pinjam Dalam Upaya Pengembangan UMKM Di Kota Jawa Tengah 2019 – 2021 - Diana Safitri; Adha Nursanjaya; Eva Mayshita; Rachma Tasya Mufida (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
The purpose of this study is to see how savings and loan cooperatives (KSP) contribute to the development of UMKM in Central Java City during the period 2019–2021. Annual reports of cooperatives, publications of related agencies, and academic literature are secondary data sources used for the descriptive method. The study analyzed the number of cooperatives, members, capital size, business volume, and credit ratio provided to the UMKM sector. The results of the study indicate that KSPs play an important role in providing access to capital, manager training, and local economic support for UMKM. However, limited human resources and complex regulations prevent KSPs from continuing to function properly. This study recommends strengthening the internal capacity of KSPs and simplifying regulations to increase the contribution of cooperatives to inclusive and sustainable economic growth in Central Java. This is because collaboration between cooperatives, the government, and the private sector is considered important to create an ecosystem that is conducive to UMKM growth.